Perceptions of Work Safety and Organizational Commitment of Low-Cost Airline Personnel after COVID-19 Pandemic - Esichaikul, Ranee; Songsoonthronwong, Chatchapon; Poonbua , Wutipark (Modern Management Frontier Journal, 2024)
The purposes of this research were (1) to examine perceived work safety and organizational commitment of low-cost airline personnel after COVID-19 Pandemic, and (2) to propose guidelines of how to build work safety of low-cost airline personnel after COVID-19 Pandemic. This research is a mixed method research. Population were management executives and employees in three low-cost airlines in Thailand. A questionnaire was used as an instrument to collect data from 390 personnel by simple random sampling. In-depth interviews were conducted with 6 management executives and 13 employees through purposive sampling. The results showed that (1) the analysis of perceived work safety of low-cost airline personnel after COVID-19 Pandemic was at a high level while organizational commitment of low-cost airline personnel was at a high level. (2) Guidelines of how to improve work safety of low-cost airline personnel include special health care for employees, budget allocation, management support and confidence, and continued sincere communication.